Real time remote symptom monitoring during chemotherapy for cancer: European multicentre randomised controlled trial (eSMART). (21st July 2021) - Maguire, Roma; McCann, Lisa; Kotronoulas, Grigorios; Kearney, Nora; Ream, Emma; Armes, Jo; Patiraki, Elisabeth; Furlong, Eileen; Fox, Patricia; Gaiger, Alexander; McCrone, Paul; Berg, Geir; et al.
Abstract: Objective: To evaluate effects of remote monitoring of adjuvant chemotherapy related side effects via the Advanced Symptom Management System (ASyMS) on symptom burden, quality of life, supportive care needs, anxiety, self-efficacy, and work limitations. Design: Multicentre, repeated measures, parallel group, evaluator masked, stratified randomised controlled trial. Setting: Twelve cancer centres in Austria, Greece, Norway, Republic of Ireland, and UK. Participants: 829 patients with non-metastatic breast cancer, colorectal cancer, Hodgkin's disease, or non-Hodgkin's lymphoma receiving first line adjuvant chemotherapy or chemotherapy for the first time in five years. Intervention: Patients were randomised to ASyMS (intervention; n=415) or standard care (control; n=414) over six cycles of chemotherapy. Main outcome measures: The primary outcome was symptom burden (Memorial Symptom Assessment Scale; MSAS). Secondary outcomes were health related quality of life (Functional Assessment of Cancer Therapy—General; FACT-G), Supportive Care Needs Survey Short-Form (SCNS-SF34), State-Trait Anxiety Inventory—Revised (STAI-R), Communication and Attitudinal Self-Efficacy scale for cancer (CASE-Cancer), and work limitations questionnaire (WLQ). Results: For the intervention group, symptom burden remained at pre-chemotherapy treatment levels, whereas controls reported an increase from cycle 1 onwards (least squares absolute mean difference −0.15, 95% confidence interval −0.19 to −0.12; P<0.001; Cohen's D effect size=0.5). Analysis of MSAS sub-domains indicated significant reductions in favour of ASyMS for global distress index (−0.21, −0.27 to −0.16; P<0.001), psychological symptoms (−0.16, −0.23 to −0.10; P<0.001), and physical symptoms (−0.21, −0.26 to −0.17; P<0.001). FACT-G scores were higher in the intervention group across all cycles (mean difference 4.06, 95% confidence interval 2.65 to 5.46; P<0.001), whereas mean scores for STAI-R trait (−1.15, −1.90 to −0.41; P=0.003) and STAI-R state anxiety (−1.13, −2.06 to −0.20; P=0.02) were lower. CASE-Cancer scores were higher in the intervention group (mean difference 0.81, 0.19 to 1.43; P=0.01), and most SCNS-SF34 domains were lower, including sexuality needs (−1.56, −3.11 to −0.01; P<0.05), patient care and support needs (−1.74, −3.31 to −0.16; P=0.03), and physical and daily living needs (−2.8, −5.0 to −0.6; P=0.01). Other SCNS-SF34 domains and WLQ were not significantly different. Safety of ASyMS was satisfactory. Neutropenic events were higher in the intervention group. Conclusions: Significant reduction in symptom burden supports the use of ASyMS for remote symptom monitoring in cancer care. A "medium" Cohen's effect size of 0.5 showed a sizable, positive clinical effect of ASyMS on patients' symptom experiences. Remote monitoring systems will be vital for future services, particularly with blended models of care delivery arising from the covid-19 pandemic. Trial registration: Clinicaltrials.gov NCT02356081 .